NOVA MUTAÇÃO DO GENE SDHD EM PACIENTES COM PARAGANGLIOMAS DO CORPO CAROTÍDEO - Rodrigues, Roger (2018)
Paragangliomas (PGLs) are neuroendocrine neoplasms that can occur throughout the body wherever there is paraganglia. Representing 0.03% of all tumours, PGLs are extremely rare. Although predominantly benign and amenable to cure by surgical ressection, up to 6% can be malignant. To date, three genes have been identified that are associated with Familial PGLs. All three encode subunits (D, B and C) of the enzyme succinate dehydrogenase complex (SDH), which is part of the Kreb's cycle and the electron transport chain. We report a novel causative frameshift mutation in the subunit D of SDH (SDHD) in a family with Carotid Body Paragangliomas. This finding contributes for extending the known mutational spectrum of SDHD, and to help the genetic counseling of this family. Noteworthy, is now possible to offer to other relatives, still sub-clinical, a predictive test that would eventually aid an early surveillance/intervention for a better prognosis.